Vitamin b12 and folic acid in the synthesis of methionine by micro-organisms - Guest, J (1960)
INTRODUCTION Nutritional and isotopic tracer studies with both animals and micro-organisms have shown that vitamin B12 and folic acid are concerned in the biosynthesis of methionine from homocysteine and a source of C1-units (e.g. serine or formaldehyde). Using washed suspensions of E.coli serine has been found to be the moat important C1-donor and requirements for p-aminobenzoic acid and cobalamin were also demonstrated with the corresponding auxotrophic strains. Soluble extracts of acetone-dried E.coli PA15 (a serine or glycine requiring strain) catalysed the formation of methionine from serine and homocysteine when an extract of the heated organism (EHC) served as the source of folic acid cofactor; no requirement for cobalamin was observed. However replacement of the SHC by tetrahydropteroylglutamic acid (PtH4G) was not possible unless the enzymic extract was prepared from acetone-dried powders of organisms which had first been grown in the presence of added cobalamin. A heat-labile, non-diffusible factor (X) was partially-purified from the extract of cobalamin-grown organisms and this factor (X) wee essential for the utilisation of PtH4G as a cofactor for the synthesis of methionine by extracts of acetone-dried organisms grown without added cobalamin. The synthesis of methionine by ultrasonic extracts of E.coli 121/176 (a cobalamin or methionine requiring strain, grown with methionine} was on the other hand dependent upon the presence of cobalamin in the reaction mixture with either EHO or PtH4G as the cofactor for C1-transfer. The object of this work was to investigate further the complexities of the methylation of homocysteine by ultrasonic extracts of Escherichia coli with particular regard to the functions of folic acid and cobalamin. EXPERIMENTAL RESULTS Section I: The Synthesis of Methionine by Ultrasonic extracts of Escherichia coli A preliminary survey of methionine formation by extracts of several strains of E.coli was made using three test systems: (I) serine as the C1-donor and EHC as the source of the folic acid cofactor, (II) serine as C1-donor and PtH4G as the cofactor for C1-transfer and (III) the formaldehyde derivative of PtH4G (CH2O-PtH4G) as both the donor and cofactor for the transfer of C1-units. Cobalamin was necessary for optimal synthesis of methionine under all conditions when extracts of cobalamin or methionine requiring strains (E.coli 121/126, 113/3) were used. With strains having no nutritional requirement for cobalamin or methionine (E.coli PA15, W, 518) cobalamin was essential under conditions II and III i.e. only with PtH4G or CH2O-PtH4G present. Quantitatively the requirement for cobalamin was similar for all cobalamin-dependent eruditions with extracts of strain PA15 and 121/176. Cobalamin could be replaced by several of its nucleotide-substiuted analogues but not by derivatives lacking the nucleotide residue. Hone of these compounds was significantly more active than cobalamin itself though 5,6-dimethylbenzimidazolylcobamide coenzyme was 2 to 3 times wore active than cobalamin for promoting the synthesis of methionine. Growth in the presence of cobalamin enhanced the ability to form methionine of ultrasonic extracts of strain 121/176 and PA15 and the requirement for cobalamin in the reaction mixture (strain 121/176, system I and II; strain PA15, system II) was eliminated if sufficiently high concentrations were present in the growth medium. In addition to the inability of PtH4G to replace EHC in the absence of cobalamin (strain PA15), PtH4G also inhibited methionine synthesis when EHC supplied the cofactor for C1-transfer. This inhibition was overcome by cobalamin which also permits the PtH4G to function as a cofactor. The synthesis of methionine by ultrasonic extracts of E.coli PA15 was proportional to the amount of extract present. Optimal synthesis occurred at 37° in phosphate buffer with an initial pH of 7.6 to 7.8 under anaerobic conditions. Glucose, DPN, ATP and Mg2+ were also essential for optimal methionine formation although glucose and DPN could be replaced by DPNH2. S-adenosyl-L-homocysteine replaced homocysteine but ATP was still required. Serine and CH2O-PtH4G were the most active C1-donors and with the former a requirement for pyridoxal phosphate was demonstrated. This was presumably for the intermediate functioning of serine transhydroxymethylase in methionine synthesis. More direct evidence for the presence of this enzyme in ultrasonic extracts was also obtained. Growth of organisms in the presence of increasing concentrations of methionine progressively repressed their ability to form methionine in cell-free extracts. Section II: The Function of Cobalamin in the Synthesis of Methionine Inhibitory analogues of cobalamin Under conditions where cobalamin was essential for the synthesis of methionine (strain 121/176, systems I, II & III; strain PAl5, systems II & III) its action was inhibited by the methylamide, ethylamide and anilide of the mono-carboxylic acids of cobalamin and by Factor B. Furthermore the anilide analogue inhibited competitively both the action of cobalamin and the cobamide coenzyme but was leas effective against the latter. The anilide analogue did not inhibit the growth of prototrophic strains of E.coli and only inhibited the growth of cobalamin or methionine requiring auxotrophs when cobalamin was the growth factor. If extracts were prepared from organisms (strain PA15) which were first grown in the presence of cobalamin, the anilide analogue inhibited methionine formation only if it was added to the growth medium together with cobalamin. The synthesis of factor (X) by ultrasonic extracts A comparison of the different activities of ultrasonic extracts and extracts of acetone-dried E.coli PA15 suggested that in the presence of cobalamin the ultrasonic extract was capable of effecting the formation (in vitro) of the factor (X) which had previously been purified from cobalamin-grown organisms and was required for the utilisation of PtH4O as a cofactor for the synthesis of methionine by extracts of acetone-dried organisms (Kisliuk & Woods). This system for the formation of X was presumably destroyed by treatment with acetone. A method using protamine sulphate was devised for the isolation of factor (X) from the products of incubating ultrasonic extracts of E.coli PA15 with cobalamin and the material was assayed by its ability to promote the synthesis of methionine by extracts of acetone-dried organisms incapable of utilising PtH4G as a cofactor. The isolated factor (X) was heat-labile, non-diffusible, unstable in acidic and alkaline environments end resembled closely the material defined by Kisliuk and Woods. The mono-substituted cobalamin-amide analogues inhibited the formation of X by ultrasonic extracts but had no effect on its function in methionine synthesis. Factor B however inhibited both the formation and function of X. A more convenient method for assaying the formation of X was developed using the anilide analogue of cobalamin. Cobalamin, glucose, DPN, ATP and Mg2+ were necessary for the optimal formation of X through DPNH2 would replace glucose and DPN; the requirements for X formation were unchanged if cobalamin was replaced by the cobamide coenzyme. The preparation of X formed with the cobamide coenzyme had the same properties as that formed with cobalamin by strain PA15. The material formed by incubating eobalmrin with ultrasonic extracts of the cobalamin auxotroph E.coli 121/176 also had similar properties. Section III: The Function of Folic Acid in the Synthesis of Methionine Pteroylmonoglutamic acids Several reduced pteroylmonoglutamic acid derivatives were active as C1-donors and cofactors tot the synthesis of methionine but as with PtH4G cobalamin was an essential component of the reaction mixture. The same reduced pteroylmonoglutamic acids, also like PtH4G, inhibited the synthesis of methionine in the absence of cobalamin when EHC supplied the folic acid cofactor (strain PA15). The presence of an aminopterin-sensitive dihydropteroylglutamic acid reductase in ultrasonic extracts of E.coli PA15 was demonstrated. The cofactor activity of dihydropteroylglutamic acid (PtH2G) in methionine synthesis was inhibited by aminopterin and amethopterin whereas the activity of PtH4G and EHC were unaffected by these anti-metabolites. This suggested that the activity of PtH2G depends on its conversion to PtH4G. Furthermore, aminopterin and amethopterin prevented the inhibitory effect of PtH2G, but not of PtH4G, on methionine formation in the absence of added cobalamin (EHC present, strain PA15). Even in the presence of concentrations of aminopterin which completely inhibited the function of dihydropteroylglutamic acid reductase, PtH4G behaved as a catalyst for the formation of methionine. This suggests that PtH4G does not serve as the final reductant for methionine methyl group formation (by its conversion to PtH2G) a mechanism which has been postulated far the synthesis of the methyl groups of thymidylic acid. Conjugated forms of folic acid Several derivatives of tetrahydropteroyltriglutamic acid (PtH4G3) resembled EHC in their ability to serve as cofactors for the synthesis of methionine by enzymic extracts of E.coli PA15 in the absence of added cobalamin. with ultrasonic extracts of E.coli 121/176 cobalamin was however still required when PtH4G3 was used as the cofactor for C1-transfer. From a consideration of stability and the cofactor activity per molecule of folic acid, one of the conjugated folic acids, N5-formyl PtH4G3, qualified as a possible active component of the EHC. PtH4G inhibited the cofactor activity of the derivatives of PtH4G3 in the same manner as it inhibited the activity of EHC (strain PA15). Finally the active folic acid components of the EHC were fractionated by chromatography on triethylaminoethylcellulose and one component was tentatively identified as N6-formyl PtH4G3 by comparing its cofactor activity, microbiological growth factor activity and its chromatographic behaviour with a sample of synthetic N5-formyl PtH4G3. DISCUSSION The most satisfactory explanation of the results so far obtained is the postulation of two mechanisms for the synthesis of methionine in Escherichia coli, one being completely dependent upon the presence of cobalamin and the other being less dependent or independent of the metabolism of cobalamin. It is suggested that the second pathway is blocked in cobalamin-requiring auxotrophs whereas other strains can use both pathways. Unlike most other C1-transfer reactions, PtH4G does not serve as a folic acid cofactor for the synthesis of methionine (unless cobalamin was present). Furthermore PtH4G appeared to he an inhibitory analogue of the natural folic acid cofactors of the EHC and of PtH4G3 and its derivatives. Nevertheless PtH4G was an active cofactor for methionine formation in the presence of cobalamin, presumably by the mechanism normally operating in the cobalamin auxotrophs. It would seem that the mechanism of C1-transfer in the formation of methionine is more complex than other C1-transfer reactions which have been examined; no specific requirement for either a conjugated folic acid cofactor or the added participation of cobalamin has previously been described. It seems certain that the function of cobalamin is mediated by a protein-like factor (X) which may contain cobalamin or a cobamide coenzyme. The exact function of cobalamin was not defined; it may however participate in either the transference of C1-units or their reduction. No other intermediates of methionine formation were isolated and it would appear that further elucidation of the mechanism of this reaction will depend on the fractionation of the enzymic extracts of several strains of Escherichia coli.